Motivators and Barriers to Entrepreneurial Intention. - Nasution, Irhamir Rahman Nasution (2007)
The main purpose of this study was to determine the relationships between motivators and barriers and its dimension to entrepreneurial intention among 312 randomly selected graduates of Universitas Sumatera Utara (USU) in Pusat Ketenaga Kerjaan (PJK) USU. The study also examined statistically significant differences in the respondents' entrepreneurial intention when grouped by gender, age, and ethnic. In assessing motivators and barriers, the questionnaire developed by Choo and Wong (2006) was adopted, pilot-tested, and used in the research. In assessing entrepreneurial intention, the questionnaire by Reitan (1997) and Peterman and Kennedy (2003) was adopted, pilot-tested, and used in the research. Statistical tools used were frequency counts, percentages, means, t-test, One-Way ANOVA, Pearson's r, and Multiple Regression Analysis. Analyses were set at 0.05 level of significance by using the SPSS (Version 12.0) computer software. Overall, the respondents "agreed" on motivators and generally "neutral" on barriers and entrepreneurial intention. Motivators and barriers by using Pearson's Correlation showed significance relationships to entrepreneurial intention. Across the motivators' and barriers' dimensions, only four out of eight dimensions showed significant relationships. Intrinsic rewards, Independence/Autonomy, Hard reality, and Compliant Cost showed significant relationships to entrepreneurial intention. There were no statistically significant differences between entrepreneurial intention and (a) gender, (b) age, and (c) ethnic.